Early outcomes after implementation of treat all in Rwanda: an interrupted time series study. Issue 4 (16th April 2019) - Ross, Jonathan; Sinayobye, Jean d'Amour; Yotebieng, Marcel; Hoover, Donald R; Shi, Qiuhu; Ribakare, Muhayimpundu; Remera, Eric; Bachhuber, Marcus A; Murenzi, Gad; Sugira, Vincent; Nash, Denis; Anastos, Kathryn; et al.
Abstract: Introduction: Nearly all countries in sub‐Saharan Africa have adopted policies to provide antiretroviral therapy (ART) to all persons living with HIV (Treat All), though HIV care outcomes of these programmes are not well‐described. We estimated changes in ART initiation and retention in care following Treat All implementation in Rwanda in July 2016. Methods: We conducted an interrupted time series analysis of adults enrolling in HIV care at ten Rwandan health centres from July 2014 to September 2017. Using segmented linear regression, we assessed changes in levels and trends of 30‐day ART initiation and six‐month retention in care before and after Treat All implementation. We compared modelled outcomes with counterfactual estimates calculated by extrapolating baseline trends. Modified Poisson regression models identified predictors of outcomes among patients enrolling after Treat All implementation. Results: Among 2885 patients, 1803 (62.5%) enrolled in care before and 1082 (37.5%) after Treat All implementation. Immediately after Treat All implementation, there was a 31.3 percentage point increase in the predicted probability of 30‐day ART initiation (95% CI 15.5, 47.2), with a subsequent increase of 1.1 percentage points per month (95% CI 0.1, 2.1). At the end of the study period, 30‐day ART initiation was 47.8 percentage points (95% CI 8.1, 87.8) above what would have been expected under the pre‐Treat All trend. For six‐month retention, neither the immediate change nor monthly trend after Treat All were statistically significant. While 30‐day ART initiation and six‐month retention were less likely among patients 15 to 24 versus >24 years, the predicted probability of both outcomes increased significantly for younger patients in each month after Treat All implementation. Conclusions: Implementation of Treat All in Rwanda was associated with a substantial increase in timely ART initiation without negatively impacting care retention. These early findings support Treat All as a strategy to help achieve global HIV targets.